University in the education through work program for health: Report of experience Ceunes-Ufes - Soprani dos Santos, Andréia; Araújo Dias, Jerusa; Alexandre, Alexandre; Bubach, Susana; Barreto Teresa Gradella, Débora; Andrade de Souza, Marco Antônio; Velez Benito, Gladys Amélia (Guará Journal, 2017)
Ministries of Health and Education, in order to reformulate public policies and interfere in learning-teaching process, founded the Education Through Work Program for Health (PET Health) and the National Program of Reorientation of Health Professional Training (PRO Health). This article reports the work in two Primary Health care Units in São Mateus, in the state of Espírito Santo. Aiming to promote interdisciplinary actions of education and health assistance, contribute to health professional training, collaborate in primary care qualification and in consolidating the National Healthcare Service (SUS) in that town. The program reveals itself as a fundamental proposal, articulates teaching and service, cooperates in the learning teaching process and favors the debate on curricular restructuring of graduation courses in the health field.